2017
DOI: 10.3892/ol.2017.5914
|View full text |Cite
|
Sign up to set email alerts
|

Combination of celecoxib and PD184161 exerts synergistic inhibitory effects on gallbladder cancer cell proliferation

Abstract: Abstract. Cyclooxygenase-2 (COX-2) and extracellular signal-regulated kinase 1/2 (ERK1/2) may serve as potential targets in various types of cancer; however, the roles of these proteins in gallbladder carcinoma (GBC) have not been reported previously. In the present study, the expression levels of COX-2 and phospho (p)-ERK1/2 in GBC were examined and the biological activities of celecoxib and PD184161 (specific inhibitors of COX-2 and p-ERK1/2, respectively) on the proliferation, cell cycle and apoptosis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Xie et al[ 35 ] conducted an in vitro experiment examining the effect of COX-2 on the angiogenesis of pancreatic cancer cells and indicated that COX-2 was positively associated with the microvascular density, promoting pancreatic cancer cell growth. Celecoxib, a selective COX-2 inhibitor, was found to enhance the effect of chemotherapeutic drugs on pancreatic cancer and inhibit the proliferation of gallbladder cancer cells[ 36 , 37 ]. Ohtsubo et al[ 38 ] confirmed that SUA regulates the expression of COX-2 through XOR in in vivo and in vitro experiments, which may explain the association between SUA and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al[ 35 ] conducted an in vitro experiment examining the effect of COX-2 on the angiogenesis of pancreatic cancer cells and indicated that COX-2 was positively associated with the microvascular density, promoting pancreatic cancer cell growth. Celecoxib, a selective COX-2 inhibitor, was found to enhance the effect of chemotherapeutic drugs on pancreatic cancer and inhibit the proliferation of gallbladder cancer cells[ 36 , 37 ]. Ohtsubo et al[ 38 ] confirmed that SUA regulates the expression of COX-2 through XOR in in vivo and in vitro experiments, which may explain the association between SUA and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, expression levels of certain miRNA strands in vitro significantly enhanced GBC proliferation and invasion [ 51 ]. The strong associations discussed above argue that there may be a role for anti-inflammatory agents in the prevention or treatment of GBC [ 52 , 53 ]. Population studies have indicated that the use of aspirin, an inhibitor of COX-2 protein, may reduce the risk of GBC (OR 0.37) [ 54 ].…”
Section: Chronic Inflammation: the Common Link Of Gallbladder Cancer mentioning
confidence: 99%
“…Population studies have indicated that the use of aspirin, an inhibitor of COX-2 protein, may reduce the risk of GBC (OR 0.37) [ 54 ]. Several in vitro studies have been performed attempting to treat GBC with various anti-inflammatory agents with promising results [ 52 ], but there have been no human trials to date.…”
Section: Chronic Inflammation: the Common Link Of Gallbladder Cancer mentioning
confidence: 99%
“…The anti-cancer effects of celecoxib are associated with the following: (i) the inhibition of the highly over-expressed tumor cyclooxygenase-2 (COX-2), which in turn has been related to the acquisition and maintenance of an invasive metastatic phenotype [ 14 ]; (ii) the activation of the intrinsic apoptosis pathway [ 15 ]; (iii) the inhibition of oxidative phosphorylation (OxPhos) [ 12 , 13 ]; and (iv) the blocking of cell migration and invasiveness [ 12 ]. The combination of celecoxib with some drugs (PD184161, ZD6474, or plumbagin) has been already successfully tested on several carcinomas (gallbladder cancer, osteosarcoma, melanoma) [ 16 , 17 , 18 ]. However, some of these latter drugs are currently still under development, and they have not yet been approved by the USA Food and Drug Administration, which will most likely delay their eventual entry into the clinic [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%